A novel contact-free atrial fibrillation monitor: a pilot study. Issue 1 (31st December 2021) - Sadeh, Ben; Merdler, Ilan; Sadon, Sapir; Lupu, Lior; Borohovitz, Ariel; Ghantous, Eihab; Taieb, Philippe; Granot, Yoav; Goldstein, Orit; Soriano, Jonathan Calderón; Rubio-Oliver, Ricardo; Ruiz-Rivas, Joaquin; et al.
Abstract: Aims: Atrial fibrillation (AF) is a major cause of morbidity and mortality. Current guidelines support performing electrocardiogram (ECG) screenings to spot AF in high-risk patients. The purpose of this study was to validate a new algorithm aimed to identify AF in patients measured with a recent FDA-cleared contact-free optical device. Methods and results: Study participants were measured simultaneously using two devices: a contact-free optical system that measures chest motion vibrations (investigational device, 'Gili') and a standard reference bed-side ECG monitor (Mindray ® ). Each reference ECG was evaluated by two board certified cardiologists that defined each trace as: regular rhythm, AF, other irregular rhythm or indecipherable/missing. A total of 3582, 30-s intervals, pertaining to 444 patients (41.9% with a history of AF) were made available for analysis. Distribution of patients with active AF, other irregular rhythm, and regular rhythm was 16.9%, 29.5%, and 53.6% respectively. Following application of cross-validated machine learning approach, the observed sensitivity and specificity were 0.92 [95% confidence interval (CI): 0.91–0.93] and 0.96 (95% CI: 0.95–0.96), respectively. Conclusion: This study demonstrates for the first time the efficacy of a contact-free optical device for detecting AF. Graphical abstract: